Evaluation of HCV-related liver fibrosis post-successful DAA therapy - Nermine Ehsan; Dina Sweed; Maha Elsabaawy (Egyptian Liver Journal, 2021)
Abstract Background The rapidly developing era of direct-acting antiviral regimens (DAAs) for more than one hepatitis C virus (HCV) genotype had certainly alleviated HCV burden all over the world. Liver fibrosis is the major dramatic complication of HCV infection, and its progression leads to cirrhosis, liver failure, and hepatocellular carcinoma. The impact of DAAs on liver fibrosis had been debatably evaluated with undetermined resolution. Main body The aim of this review is to accurately revise the effects of DAA regimens on liver fibrosis which can either be regression, progression, or non-significant association. Liver fibrosis regression is a genuine fact assured by many retrospective and prospective clinical studies. Evaluation could be concluded early post-therapy reflecting the dynamic nature of the process. Conclusions The ideal application of DAA regimens in treating HCV has to be accomplished with efficient non-invasive markers in differentiating proper fibrosis evaluation from necroinflammation consequences. Liver biopsy is the gold standard that visualizes the dynamic of fibrosis regression.